The Texas special education cap: Exploration into the statewide delay and denial of support to students with disabilities - David E. DeMatthews; David S. Knight (Arizona State University, 2019)
State accountability systems have been a primary school reform initiative in the U.S. for the past twenty years, but often produce unintended negative consequences. In 2004, the Texas Education Agency (TEA) implemented the Performance Based Monitoring and Analysis System (PBMAS) which included an accountability indicator focused on the percentage of students found eligible for special education under the Individuals with Disabilities Education Act (IDEA), the nation's special education law. From 2004 through 2016, the percentage of students found eligible for special education in Texas declined significantly, while the national rate held constant. Eventually, the U.S. Department of Education (ED) investigated TEA and the statewide implementation of IDEA. The purpose of this study is two-fold: (a) to evaluate the potential impact of the the PBMAS indicator on manipulation of special education identification practices; and (b) to describe how the indicator may have influenced school and district personnel. We highlight several concerning trends in state and district data and, through an analysis of publicly available reports from the ED, show how district and school personnel knowingly and unknowingly acted in ways that delayed and denied special education to potentially eligible students. We conclude with recommendations for TEA and implications for future research and policy.